Discontinuation of statin therapy in older people: does a cancer diagnosis make a difference? An observational cohort study using data linkage. Issue 3 (21st May 2012) - Stavrou, Efty P; Buckley, Nicholas; Olivier, Jake; Pearson, Sallie-Anne
Abstract : Objective: The aim was to examine statin discontinuation rates in a cohort of elderly Australians with newly diagnosed cancer using population-based secondary health data. Design: Observational cohort study. Setting: New South Wales, the largest jurisdiction in Australia. The Pharmaceutical Benefits and Repatriation Pharmaceutical Benefits Schemes are national programmes subsidising prescription drugs to the Australian population and Australian Government Department of Veterans' Affairs clients. Participants: The cohort comprised 1731 cancer patients aged ≥65 years with evidence of statin use in the 90 days prior to diagnosis. They were matched to 3462 non-cancer patients prescribed statins in the same period. Main outcome measure: The authors compared statin discontinuation rates up to 4 years post-diagnosis and examined the factors associated with statin discontinuation. Results: The proportion of cancer patients discontinuing statin therapy at 4 years (27%) was comparable to the comparison cohort; however, significantly higher proportions of the cancer cohort discontinued statins than the comparison cohort at 3, 6 and 12 months of follow-up (9.7% vs 7.4% at 12 months, respectively). More than 30% of cancer patients who died were dispensed statins within 30 days of death. Discontinuation of statin therapy in cancer patients was associated with regionalised and distant disease spread at diagnosis (p<0.001), older age (p=0.006), upper gastrointestinal organs and liver cancer (aHR 2.95, 95% CI 1.92 to 4.53) and cancer of the lung, bronchus and trachea (aHR 1.99, 95% CI 1.32 to 3.00) and poorer survival. Conclusions: Medications should be rationalised at the time of a cancer diagnosis, especially in the setting of a poor prognosis. At least for some patients in our cohort, statin therapy may be inappropriately continued which adds unnecessarily to therapeutic burden.